Efeito de um programa sistematizado de danças no controle postural de pacientes com doença de Parkinson - Fiorio, Lucas Meira [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Postural instability is one of the cardinal signs of Parkinson's disease (PD). Previous studies have suggested that postural instability is not responsive to antiparkinsonian medication. Therefore, other ways of treatment should be investigated to improve postural control, such as physical exercise. Dance has been widely studied in people with PD; however, there are few studies about the effects of dance on postural control measures (center of pressure - CoP). AIM: To verify the effects of a dance program on postural control measures in people with PD and its maintenance after 5 months (follow-up). METHODS: Fifty-three individuals with PD, between stages 1 and 3 of the Hoehn & Yahr scale, were randomly distributed in 2 groups: Dance Group (DG: n = 28) and Control Group (CG: n = 25). The activities of both groups were performed in the Physical Activity Program for patients with Parkinson's disease (PROPARKI) over six months, three sessions per week, with a duration of 1h per session. The activities of the DG were based on different styles and musical rhythms and had as a proposal: the use of different bases of supports and the increase of the complexity of the choreographic sequences. The CG performed leisure, speech and language activities. The participants performed the assessments in three moments: pre-training, post-training, and follow-up. The postural control assessment was performed by the CoP analysis, through a force platform (200 Hz) in two experimental conditions: (i) simple task and (ii) double task (three trials per condition). The CoP variables analyzed were: displacement, mean velocity, root mean square in both anteroposterior (AP) and mediolateral (ML) directions, and the displacement area. RESULTS: ANOVA revealed interaction between group and moment for ML displacement (F2,102 = 3.24, p = 0.04) and ML mean velocity of CoP (F2,102 = 3.22, p = 0.04). Post-hoc tests showed that while the CG increased ML displacement and velocity...

A instabilidade postural é um dos sinais cardinais da doença de Parkinson (DP). Estudos anteriores sugerem que esta instabilidade é pouco responsiva ao tratamento medicamentoso para DP. Com isso, outras formas de tratamento devem ser investigadas para melhora do controle postural, como o exercício físico. A dança tem sido amplamente estudada em idosos com DP, entretanto há poucos estudos sobre os efeitos da dança em medidas do controle postural (centro de pressão - CoP). OBJETIVO: Verificar os efeitos de um programa de dança em medidas do controle postural em pacientes com DP e sua manutenção após um período de 5 meses (follow-up). MÉTODOS: Cinquenta e três idosos com DP, entre os estágios 1 e 3 da escala Hoehn & Yahr, foram distribuídos randomicamente em 2 grupos: Grupo Dança (GD: n=28) e Grupo Convívio (GC: n=25). As atividades de ambos os grupos foram realizadas no Programa de Atividade Física para pacientes com doença de Parkinson (PROPARKI), durante seis meses, três vezes por semana com duração de 1h por sessão. As atividades do GD eram baseadas em diferentes estilos e ritmos musicais e teve como proposta: o uso de diferentes bases de suportes e o aumento da complexidade das sequências coreográficas. O GC realizou atividades de lazer e fonoaudiologia. Os idosos realizaram as avaliações em três momentos: pré-treino, pós-treino e follow-up. A avaliação do controle postural foi feita pela análise do CoP, por meio de uma plataforma de força (200 Hz) com duas condições experimentais: (i) tarefa simples e (ii) tarefa dupla (três tentativas por condição). As variáveis do CoP analisadas foram: deslocamento, velocidade média, root mean square, ambas no sentido anteroposterior (AP) e médio lateral (ML) e a área do deslocamento. RESULTADOS: A ANOVA revelou interação entre grupo e momento para as variáveis de deslocamento ML (F2,102 = 3,24; p = 0,04) e velocidade ML (F2,102 = 3,22; p = 0,04)...
Keywords: Dança; Doença de Parkinson; Terapia pela dança; Exercícios físicos; Postura humana